HYBRID AUTHORITY AT THE INTERSECTION OF CONSTITUTION AND SHARIA: JURISDICTIONAL DILEMMAS AND THE ENFORCEMENT OF ISLAMIC FAMILY LAW IN NIGERIA - Thomas Sheku Marah; Nura Sani Yusuf; Jelly Akter; Hoda Gueddi; Sulaiman Dalha Ahmad; Abubakar Muhammad Jibril (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2026)
Purpose – This study examines why the constitutional recognition of Sharia family courts in Nigeria has failed to resolve ongoing tensions over power, legitimacy, and jurisdiction, revealing a structural dilemma in which constitutional supremacy and Sharia authority coexist without meaningful integration. Methods – This study uses a normative legal method based on doctrinal analyses. Primary data include constitutional provisions and legal instruments governing Sharia courts, while secondary data consist of established scholarly studies on Islamic legal theory, constitutional law, and legal pluralism. Data were analyzed using interpretive and analytical techniques to assess jurisdictional structures, sources of authority, and adjudication patterns. Findings – These findings show that Islamic family law in Nigeria operates through a dual structure of constitutional legality and religious legitimacy, resulting in the persistent fragmentation of authority that produces doctrinal inconsistency, judicial minimalism, and institutional caution. Rather than offering a principled framework for coexistence, constitutional supremacy functions primarily as a mechanism of subjugation, placing Sharia family law in a state of formal validity but with normative uncertainty. Thus, the stability of Islamic family law does not arise from the resolution of conflicts of authority but rather from the ability of the judicial system to manage normative tensions through case-specific accommodations within a stable but conceptually fragile space of legal pluralism. Research contribution/limitations – This study is limited to normative legal analysis and does not include empirical court data or litigants’ perspectives. Therefore, the conclusions cannot be generalized beyond doctrinal interpretations. Originality/value – This study offers a conceptual reframing of Islamic family law as a semi-autonomous normative subsystem within the constitutional order, contributing to the debate on legal pluralism and religious courts.